Biogeography of Dolichospermum lemmermannii (Nostocales, Cyanobacteria) in European waterbodies: a multidisciplinary approach - Capelli, Camilla; Cerasino, Leonardo; Salmaso, Nico; Ballot, A. (2016)
The presence of Dolichospermum lemmermannii was documented in northern temperate and boreal regions, between the 40th parallel and the Arctic Circle. In the last decade, this species spread towards southern Europe, making its appearance also in the largest lakes south of the Alps (Garda, Iseo, Como and Maggiore). Extended surface water blooms of this species were observed in Lake Garda at the beginning of the 1990s, and afterwards in lakes Iseo (second half of the 1990s), Maggiore (2005), and Como (2006). Blooms were always observed in summer and early autumn, during calm weather. The study of sub-fossil akinetes preserved in core sediments allowed antedating the introduction of this species in Lake Garda in the middle of the 1960s. The significant increase in water temperatures and nutrient enrichment of the lake seemingly supported the development of this species in the successive decades. Global warming is indeed considered one of the major factors favouring the invasion of Nostocales, particularly due to the ability of the large gas-vacuolated species belonging to this group to control vertical movements in stratified water columns. The large perialpine lakes are a renewed tourist destination and an important source of water for drinking, irrigation and industry. The appearance of Dolichospermum in this group of lakes represents a new potential risk because of the previous identification of several toxigenic populations associated with animal poisoning events in northern European countries. Despite serious concerns raised by the ecological, health and economic impacts, a comprehensive taxonomical, ecological, and toxicological study was begun only very recently. The variability of morphological features in natural populations of D. lemmermannii are quite wide and some strains showed high temperature optima. The recent expansion towards the south highlights the ecological heterogeneity of this species and the conceivable existence of different ecotypes. In this work, we report the results of a wide research ...